ANALISIS WARNA DALAM MEDIA INSTAGRAM PADA CITRA MEREK KASOEM VISION CARE DAN VIUUM - Abimantrana, Lintang (Kartala, 2025)
Abstract Color Analysis of Brand Image of a brand is a strategy of branding activities. Visual influence has a tremendous impact on consumer perception. Through the visual elements presented, it can communicate the brand to consumers. The Vision and Mission of the brand are also seen when presenting its visual identity in the media. One of the visual elements that can communicate is color. Color elements can contribute to conveying the message and image of a brand. In this case, the optical brand that is a pioneer in Indonesia is Kasoem Vision Care. This optical brand has a competitor named VIUUM, which continues to present visual messages as a medium of communication to customers. This study uses a qualitative descriptive research method, while the approach used is a case study approach to see what the two optical brands want to convey. By analyzing the color emotion guide in color theory, this study shows the results of the tendency to use the same so that it can identify the two brands using primary colors as their identity to gain attraction and build the desired perception of the two optical brands. Keywords: Brand, Visual Identity, Colour, Brand Image